Metal geochemistry in suspended and bed sediments in the eutrophic lowland Salado River basin (Buenos Aires, Argentina) - Tatone, Leandro Martín (2021)
The Salado River is a lowland river that drains a vast and productive region of central Argentina into the Río de la Plata estuary. To evaluate water quality and the geochemistry of major and trace metals (Fe, Mn, Zn, Cu, Pb, Cr and Ni), water and sediments samples were collected along 500 km of the Salado River basin (n = 21). Waters were highly alkaline (pH: 8.8 ± 0.4), saline (5.2 ± 1.8 mS/cm), turbid (467 ± 237 NTU) and eutrophic (chlorophyll a: 187 ± 119 µg/l) with a decreasing gradient towards the river mouth reflecting the contribution of alkaline ground waters and eutrophication at the river head. Suspended particles (70–595 mg/l) were enriched in total organic carbon, nitrogen (5–7 times) and metals (1–4 times) relative to bed sediments, but metal concentrations were 2–10 times below the world river’s average. Consistently, metal concentrations in bed sediments were lower than sediment quality guidelines with an increasing downriver trend following the enrichment of clays. The enrichment factors (EF) and geoaccumulation index (Igeo), calculated with local background metal levels from the deepest layers of a dated sediment core, indicate a general prevalence of natural metal sources (EF < 1.5) with unpolluted sediments (Igeo ≤ 0), excepted for the Chivilcoy stream, which showed a significant enrichment of Zn, Cu and Pb (EF = 2–12; 0 ≤ Igeo ≤ 1) constituting a clear pollution hot spot in the basin.